Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fnmol.2018.00137
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wnt and Notch-Responsive Lgr5+ Hair Cell Progenitors in the Striolar Region of the Neonatal Mouse Utricle

Abstract: Dysfunctions in hearing and balance are largely connected with hair cell (HC) loss. Although regeneration of HCs in the adult cochlea does not occur, there is still limited capacity for HC regeneration in the mammalian utricle from a distinct population of supporting cells (SCs). In response to HC damage, these Lgr5+ SCs, especially those in the striolar region, can regenerate HCs. In this study, we isolated Lgr5+ SCs and Plp1+ SCs (which originate from the striolar and extrastriolar regions, respectively) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 80 publications
2
30
0
Order By: Relevance
“…Indeed, evidence in that study indicates that EGFR signaling can lift the p27 kip1 inhibition of proliferation in the dissociated SCs, and suggests that a PI3K-dependent pathway appears to play a role in the p27 kip1 -independent proliferation of that subset of dissociated SCs from the neonatal mouse cochlea. The mitogenic effect of GSK3 inhibitors in neonatal HC epithelia is also well documented (Lu and Corwin, 2008;Roccio et al, 2015;Samarajeewa et al, 2018;You et al, 2018). Our results suggest that the stimulatory effects of these agents are closely linked with their capacity to remodel junctions once SCs have matured.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, evidence in that study indicates that EGFR signaling can lift the p27 kip1 inhibition of proliferation in the dissociated SCs, and suggests that a PI3K-dependent pathway appears to play a role in the p27 kip1 -independent proliferation of that subset of dissociated SCs from the neonatal mouse cochlea. The mitogenic effect of GSK3 inhibitors in neonatal HC epithelia is also well documented (Lu and Corwin, 2008;Roccio et al, 2015;Samarajeewa et al, 2018;You et al, 2018). Our results suggest that the stimulatory effects of these agents are closely linked with their capacity to remodel junctions once SCs have matured.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, most of the sensorineural deafness induced by gene mutation, noise, different ototoxic drugs, inflammation, or aging are caused by the HC loss [52][53][54][55][56][57]. However, the mammals only have very limited HC regeneration ability; most of the damaged HCs cannot be spontaneously regenerated, which make the HC loss and hearing loss to be irreversible [58][59][60][61][62]. CIs are the most efficient clinical therapeutic devices for sensorineural deafness patients, and recent studies have shown that application of CI-based electric acoustic stimulation together with multiple biomaterials also can promote the differentiation of neural stem cell [63][64][65][66] and promote maturation of spiral ganglion neuron [67][68][69][70].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that a limited number of HCs can be regenerated in newborn mice from SCs and inner ear progenitor cells, and several studies have shown that many important signaling pathways are involved in HC regeneration, such as Wnt, Notch, and Shh [7,8,[11][12][13][14][80][81][82][83][84]. Many other genes and related pathways have also been shown to play important roles in HC regeneration [85,86], and these pathways might have crosstalk with each other to affect the proliferation and differentiation of SCs and Lgr5+ progenitors [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…HC loss is irreversible in adult mammals, whereas HCs can be regenerated from supporting cells (SCs) in the inner ear of birds and fish [1]. Recent studies have shown that in newborn mice, HCs can also be regenerated from SCs, especially from a subset of Lgr5+ progenitor cells [2][3][4][5][6][7][8]. However, this regenerative ability is quickly lost as the mice age [2-4, 9, 10].…”
Section: Introductionmentioning
confidence: 99%